Low frequency modes in summer monsoon circulation over India (MAUSAM, 1988)
In recent years there has been a large number of investigations on the structural features of 30-60 day oscillations during the summer monsoon of the southeast Asia. However, most of the investigations are based on the 1979 MONEX data. In the present investigation, the nature of this near 40-day mode has been studied using a comprehensive data set for SIX years over the Indian sub-continent. The study reveals that the periodicity of this mode has a significant inter-annual variability and during the same year it has a strong spatial dependence. Finally the limitations of the use of this mode in foreshadowing the changes of summer monsoon circulations over India have been discussed.